Determination of Binding Interactions of Human Carbonic Anhydrase XII - Mrunmayee P. Toraskar (Novel Aspects on Pharmaceutical Research Vol. 1, 2023)
Tumors are tissues containing hypoxic regions and producing metabolic acids. Cancer cells decreases the pH and foster tumor growth and progression. Carbonic anhydrase plays important role in maintaining acid base balance in various types of cells. Human CA XII is membrane CA which is overexpressed in tumors. Therefore, objective of the study involved determination of binding interactions of hCA XII with the designed molecules as N’-(substituted phenyl sulfonyl)-pyridine-2- carbohydrazide derivatives and N’-(substituted phenyl sulfonyl)-thiophene-2-carbohydrazide derivatives. Binding interactions of the selected ligands were studied using glide module of Schrodinger software using Maestro 10.1 interface. X-ray crystallographic data showed that the metal ion is coordinated by three histamine residues (His 94, His 96, and His 119) and a water molecule/ hydroxide ion. In order to compare the effectiveness of these ligands as selective human carbonic anhydrase (hCAXII) inhibitors to the industry-standard inhibitor Acetazolamide, docking scores as well as 2D and 3D binding interactions of these ligands were examined at the conclusion of molecular docking studies. (AZA). The ligands’ conformation and binding interactions with hCAXII were remarkably similar to those of the standard. As a result, it can be inferred that the chosen ligands may have a high affinity for hCAXII and may have the ability to inhibit this enzyme.